1999
DOI: 10.1046/j.1365-2168.1999.01154.x
|View full text |Cite
|
Sign up to set email alerts
|

During liver regeneration following right portal embolization the growth rate of liver metastases is more rapid than that of the liver parenchyma

Abstract: In functionally intact liver parenchyma, during hepatic regeneration or hypertrophy, the growth rate of metastases is more rapid that that of the liver parenchyma. However, a wide variation in growth rate is observed between patients and between metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
177
1
25

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(208 citation statements)
references
References 14 publications
5
177
1
25
Order By: Relevance
“…PVE increases the anticipated future liver volume and allows surgery in patients who would otherwise be contraindicated for resection. The potential disadvantage of PVE is that earlier studies have suggested that it may stimulate tumour growth and lead to reduced long-term survival (Elias et al, 1999;Kokudo et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PVE increases the anticipated future liver volume and allows surgery in patients who would otherwise be contraindicated for resection. The potential disadvantage of PVE is that earlier studies have suggested that it may stimulate tumour growth and lead to reduced long-term survival (Elias et al, 1999;Kokudo et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…This may reflect either a rapid disease progression in patients who are selected for PVE or that PVE stimulates tumour growth. Tumour growth exceeding that of the normal liver parenchyma has been shown on imaging following PVE in patients with contra lateral lobe metastases (Elias et al, 1999), and the tumour-doubling time following PVE has been shown to be reduced from 92 to 76 days (Kokudo et al, 2001). There have been concerns that PVE may increase the risk of disease recurrence after curative resection (Kokudo et al, 2001;Pamecha et al, 2009).…”
mentioning
confidence: 99%
“…Analogical progression of primary and secondary tu- mors after foregoing resection was also noted in experimental [58][59][60] and clinical [61,62] studies. Partial heaptectomy impacted on the growth of tumor size in the remaining places of diseased liver.…”
Section: The Hypothesis Of Genome Intrusionmentioning
confidence: 62%
“…Since the first description of the potential of intrahepatic tumor enlargement after PVE (24), accumulating evidence has shown that PVE stimulates tumor growth in both embolized and non-embolized liver segments (13,25). Hayashi et al (26) reported that the median tumor growth rate of primary liver cancer in the embolized lobe after PVE was approximately two times greater than that before PVE.…”
Section: Discussionmentioning
confidence: 99%